Meta-analysis of flipped classroom model to promote mathematical higher-order thinking - Novita Fatmiyati; Dadang Juandi; Siti Fatimah (Journal of Education and Learning (EduLearn), 2026)
Numerous studies have explored how the flipped classroom affects satisfaction, learning outcomes, and attitudes of both teachers and students. However, there is a gap in research regarding its impact on higher-order thinking. This meta-analysis aims to fill this gap by assessing the effect size of the flipped classroom model on students’ mathematical higher-order thinking. Data from 30 primary studies, including journal articles, proceedings, theses, and dissertations, were analyzed using Comprehensive Meta-Analysis (CMA) Version 4 Software. These studies included 1,043 students in the experimental groups and 970 in the control groups. The analysis revealed a pooled effect size of 1.094, indicating a significant positive impact. Notably, the effect size remained consistent across various educational levels, sample sizes, years of study, types of learning media, and higher-order thinking indicators. This suggests the versatility and effectiveness of the flipped classroom model across different educational settings, including middle school, high school, and college, regardless of class size or learning media used.